Chondroblastoma of the femoral head: curettage without dislocation - Di Yang; Haiping Ouyang; Ziyu Zhou; Zhongliang Wang (BMC Surgery)
Abstract Background Chondroblastoma (CBL) of the femoral head is a rare disease, typically encountered in the epiphysis of long bones, with its occurrence in the femoral head being particularly uncommon. The unique location and aggressive nature of this tumor pose substantial challenges in its treatment, leading to ongoing controversies regarding the therapeutic approaches. In this study, we introduce a technique of curettage without surgical dislocation as a treatment option for CBL in this challenging location. Methods A total of 6 children diagnosed with chondroblastoma of the femoral head underwent a surgical procedure consisting of curettage, the application of anhydrous alcohol as an adjuvant therapy, followed by bone grafting. The epiphyseal plate status of the femoral head was classified as open, closing, or closed. To evaluate the children's postoperative functional outcome, the Musculoskeletal Tumour Society (MSTS) scoring system was utilized. Additionally, the Lodwick classification was employed to assess the extent of bone destruction. Furthermore, the kappa coefficient was calculated to quantify the level of inter-observers agreement in assessing the status of the epiphyseal plate. Results The epiphyseal plate status was closing in two patients and closed in four patients. According to the Lodwick classification, one patient was classified as IA, one as IB, and four as IC. The mean MSTS score was 28. Notably, one patient developed a femoral neck fracture three months post-curettage. Conclusions Curettage without surgical dislocation, combined with the use of anhydrous alcohol as an adjuvant therapy, followed by bone grafting, constitutes an effective treatment technique for femoral head chondroblastoma.